Interview with Subhash Mukhapaddhya, revolutionary poet, on revolutionary cultural movement in 1940s, interviewed by Kabir in Calcutta - Kabir, Shahriar.
Interview with Subhash Mukhapaddhya, revolutionary poet, on revolutionary cultural movement in 1940s, interviewed by Kabir in Calcutta.